Always Something Missing: Giving without Intention among Sino-Taiwanese Protestants and Others. Issue 1 (1st March 2022) - Breen, Gareth
Abstract: What does it take to experience grace? I argue that for followers of the Chinese Christian reformers Watchman Nee and Witness Lee, in China, Taiwan, and the United States, grace is experienced as an intended gift with a missing motivating intention. For a group in which God's intentions are rigorously mapped out, experiencing God's grace is thus no simple feat. In particular, I show how the experience of grace occurs in moments of apparent wrongdoing when reward is least comprehensible. As this wrongdoing becomes institutionalised as an ideal mode of grace, however, it paradoxically becomes less grace-ful in practice. Therefore, grace here is an inherently transgressive, destabilising, contradictory phenomenon. Extrapolating beyond Nee and Lee's followers, I suggest that at a time of gratitudinous secularism, of givenness without a Giver, blessedness without a Blesser, grace is more abundant than ever. But that with this grace comes gratitude, an emotion often resistant to social change.